Presenting a Geomorphological Conceptual Model of Construction of bridges in urban floodway- river valleys - Esmaiel Najafi; Amir Safari; Ezatoalah Ghavavati; Amir Karam (تحقیقات کاربردی علوم جغرافیایی)
Geomorphology is related to the processes and forms of the earth's surface, and any human activity, including the construction of bridges, leads to quantitative and qualitative changes in the movement and displacement of materials and kinetic energy and affects the geomorphic system, is the concern and involvement of geomorphologists. Geomorphology, as a systematic science can also study and explain the environmental realities that have been objectified in the form of processes and forms in nature, and introduce their results and output spatially in the form of maps and models. The type of research is applied and the research method is descriptive-analytical and based on the results of the Ph.D. Thesis entitled "Geomorphological modeling of the construction of bridges in urban floodways (Case study: Tehran metropolis)". The results indicate the capability and application of geomorphology in modeling and optimal location and construction of bridges, in order to create more security and welfare of citizens, reduce costs and prevent financial and human losses due to the destruction and improper location of such structures in an urban floodway- river valleys and other natural environments. Also, this study, while enriching the literature of the field in question, has studied, explained, and conceptually modeled the role and application of geomorphology in the optimal location and construction of bridges in urban issues. Keywords: Geomorphology, Conceptual Model, urban floodway- river valleys, Bridge Construction.